Prevalence of aflatoxin contamination in red chilli pepper (Capsicum annum L.) from India. (24th May 2021) - Rajendran, Sasireka; Shunmugam, Ganapathy; Mallikarjunan, Kumar; Paranidharan, Vaikuntavasan; Venugopal, Arun Prasath
Summary: The aflatoxin contamination of chilli pepper grown and marketed in Tamil Nadu, a southern Indian state, was assessed. Chilli samples were collected at different stages of the value chain and were quantified using the enzyme‐linked immunosorbent assay (ELISA) test. Forty‐two representative samples were collected from four districts identified as the hub for production, distribution, agro‐processing industries and retail stores. In addition, interviews were conducted among the chilli farmers, vendors and agro‐industrialists across the hubs to assess their knowledge on aflatoxin contamination and safe handling practices. The maximum aflatoxin content determined in the chilli pepper was 37.8 µg kg −1 . Almost 66.7% of samples collected from the retail outlets had aflatoxin values above 10 µg kg −1 . The total aflatoxin content in the samples collected across the value chain was in the range of 3.83 to 37.80 µg kg −1 . Statistical analysis on aflatoxin contents showed that there were significant differences ( P < 0.05) between the districts representing different operations of value chain. The detected aflatoxin content was highest in samples collected from Dindigul district and least in Erode district. The results of the perception study showed that respondents into farming and trade activities had very little or no knowledge of aflatoxin contamination of chilli. The prevalence of unacceptable levels of aflatoxin in the chilli supply chain in the districts studied is probably due to tropical climatic conditions and poor handling practices of chilli. Abstract : Analysing the status of aflatoxin contamination in red chilli pepper.